A new kind of resin-based wet friction material: Non-woven fabrics with isotropic fiber networks as preforms - Yewei Fu; Le Zhou; Tao Yin; Zhongyao Luo; Hejin Li; Lehua Qi (Friction)
Abstract As an alternative to short fibers, non-woven fabrics (NWFs) were made using different types of long fibers to optimize the performance of paper-based friction materials and their technology. In this investigation, the fillers and resin were impregnated into these NWFs to prepare three kinds of wet friction material. The tribological, mechanical, and thermal properties of the new wet friction material were studied. The results indicate that the dynamic friction coefficient of the new friction material is approximately 0.12 and the static friction coefficient is approximately 0.15; the better wear rate is 0.81334 × 10-14 m3·(N·m)-1. In addition, the temperature for 10% mass loss yielded 100 °C enhancement and the tensile strength was improved by 200%, compared to previously reported values. Most importantly, the advantages include a simple preparation flow, low cost, and resource conservation. This is a promising approach for the future development of paper-based friction materials.